PENANAMAN NILAI MORAL DAN SPIRITUAL ANAK MELALUI SERIAL ANIMASI ISLAMI - Faizatul Widat; Mir’atud Dayyani (JCE (Journal of Childhood Education), 2022)
Instilling Moral and Spiritual Values in Children Through Islamic Animation Series. The purpose of this study was to determine the inculcation of children's moral and spiritual values through an Islamic animated series. This type of research is a qualitative method using a case study which was carried out in September at PAUD Anak Sholih Karanganyar Paiton Probolinggo. The research subject here is one of the teaching staff of PAUD Anak Sholih. Analysis of the data that has been collected by means of observation, interviews and documentation. The results of the study show that the inculcation of moral and spiritual values in Islamic animated series children becomes better by habituating good behavior every day. The involvement of inculcating the moral and spiritual values of children is a solution for teachers and parents in instilling moral and spiritual values for the development of the golden age to the next level.